Turgenev as Perceived by Mark Aldanov - Vladimir V. Shadursky (Russian Academy of Sciences. A.M. Gorky Institute of World Literature, 2020)
The paper examines various aspects of the perception of I.S. Turgenev’s personality and works by Mark Aldanov. The reception of Turgenev in Aldanov's work has been studied diachronically: from mentioning the characters of the novel “Rudin” in the journalistic book “Armageddon” to reviews of the émigré editions of Turgenev's works and criticism in the philosophical dialogues “Ulm Night”. The reasons for Aldanov’s irony towards some of Turgenev's works, called by him the “chocolate factory”, are investigated. Aldanov's position is largely due to the principles of the cultural-historical method. Aldanov explains Turgenev's artistic failures by mistakes in a constant search for an adequate form for expressing rich content. Aldanov tries to be an objective, well-reasoned critic, but he correlates the shortcomings of Turgenev's style with the advantages of L.N. Tolstoy’s style. At the same time, Aldanov is concerned of Turgenev’s “failures”, praising him as one of the five best authors of the “golden” age of Russian literature and an original European intellectual. Aldanov mentions Turgenev in his journalism, criticism, correspondence, uses Turgenev's motives and quotes in his own fiction. The paper describes the novels “The Story of Death”, “Delirium”, “Suicide”, in which Turgenev's biography, images of Turgenev's works are embedded in the life of Aldanov's fictional characters. The kindness and morality of Turgenev's characters, the delicacy of the writer’s discourse enter the moral world of Aldanov's characters. For almost 40 years Aldanov quoted Turgenev's works and letters and used the images of his novels and stories to express his own aesthetic assessment. A sense of his own place in literature gave Aldanov the right to express his opinion not only about the merits of Turgenev's work, but also about the shortcomings of his technique.